UPAYA PENINGKATAN HASIL BELAJAR IPA MATERI CUACA DAN PENGARUHNYA BAGI MANUSIA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVMENT DIVISION (STAD) - Eyunike Pebrianti; 2Mestorine Lumbantobing (Fakultas Ilmu Pendidikan Universitas Sari Mutiara Indonesia, 2018)
The purpose of this study is to improve student learning outcomes on natural science subjects weather material and influence for humans through the implementation of student teams achievment division (STAD).The type of research used is classroom action research (CAR) consisting of II cycles. Each cycle carried out though 4 strages namely planning, implementation, observation, and reflection. Research data obtained through observation and test. The results of data analysis showed an increase in student activity and teacher activity in cycle I and cycle II. Student learning outcomes with clasical learning completeness increased by 39,40% namely from 30,30% in the pre cycle to 69,70% in the cycle I and in the second cycle increased by 21,20% namely from 69,70% in the cycle I to 90,90% in the second cycle. It can be concluded that the use of student teams achievment devision (STAD) model improve of learning outcomes of natural science subject in grade III SD Swasta Bakti Luhur year 2018/2019.